Expertise and gender effects on spatio-temporal, physiological and psychometric responses in 400-m freestyle swimming - Schnitzler, C.; Ernwein, V.; Seifert, L.; Chollet, D. (First international symposium sciences and practices in swimming, 2006)
We examined the spatio-temporal, physiological and psychometric responses during and after a 400-m freestyle swim at two distinct skill levels. Thirty-four men and women were defined as either expert or recreational swimmers, and performance parameters during a 400-m freestyle swim trial were compared. For every 25 m, video analysis provided the mean speed (V25), stroke rate (SR), stroke length (SL), and speed variability (V25var). Peak heart rate (HRp) and lactate (Hlap) values were determined, as well as the recovery kinetics for heart rate (ITR3.) and lactate (%Hlar). Subjective workload (TWL) was assessed by the NASA-TLX questionnaire. Neither expertise nor gender affected HRp or TWL. The Hlap was higher in men, in line with the literature, but exhibited no expertise effect. Inversely, the experts exhibited less V25var and greater SL than the recreational swimmers. The experts also exhibited higher %Hlar (8.6±7.18% vs. 1.65±8.2%) and ITR3' (-38.5±5.5% vs. -31.1±5.4%). The 400-m freestyle appears to require the same amount of effort from both skill levels and genders. Moreover, the methodology presented here assesses technical efficiency and physiological recovery. This systemic approach could serve as a basis for a true "diagnosis" of performance.